HUBUNGAN TRANSAKSI DENGAN PIHAK-PIHAK YANG MEMILIKI HUBUNGAN ISTIMEWA DAN KUALITAS AUDITOR DENGAN PRAKTIK MANAJEMEN LABA - FEBRIANTO, RAHMAT; WIDIASTUTY, ERNA (Jurnal Ilmiah Akuntansi dan Bisnis, 2010)
This research aims to answer two questions. First, whether related party transactions relate to earnings management and, if they do, which transaction, among those reported, that correlate with earnings management? Second, since those transactions are characterized by their complexities and those complexities, then, relate to information asymmetry, does auditor quality can mitigate earnings management practice? We choose non-financial related firms as our samples. Those 45 chosen firms were listed from 1996 to 2006 on JSX. We conduct tests based on full samples and split samples. Samples are divided based on the size of their accounting firms. Results show that two out of six related party transactions measures are statistically related to earnings management. Moreover, samples audited by bigger accounting firms have higher abnormal accruals than samples audited by smaller accounting firms. This result implies that the earlier manage their earnings number. Even though our results are not consistent among different measures of related party transactions, we, however, can conclude that opportunistic managers can take advantage of the transactions complexities. We argue that standards must be reconsidered how those transactions should be disclosed to public. Auditors must be made aware of the consequences to them of not being aware of this opportunistic behavior.
Keywords: related party transactions, earnings management, auditor quality.